2004
DOI: 10.1023/b:jots.0000022616.03662.2f
|View full text |Cite
|
Sign up to set email alerts
|

Social attitudes toward traumatized men and women: A vignette study

Abstract: This study investigated social beliefs about gender-appropriate reactions to trauma. Ninety-three men and 179 women completed vignette measures of attitudes toward victims, the Bem Sex Role Inventory, and the Trauma History Questionnaire. Participants evaluated male victims less favorably than female victims. Women responded more positively toward all victims than men. Participants regarded female crime victims more positively than their male counterparts, but did not distinguish between male and female natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
2
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 28 publications
(20 reference statements)
2
23
2
2
Order By: Relevance
“…This finding supported previous research that has suggested that males are generally rated less favorably than females (Corrigan, Markowitz, Watson, Rowan, & Kubiak, 2003;Daoud, 2009;Snyder & Berscheid, 1977). Mendelsohn and Sewell (2004) also reported that women responded more favorably than men towards all victims, and those individuals who were rated as femininesex-typed rated victims more favorably than participants who were rated as being masculine-sextyped. This study also suggests that males who have been trauma victims themselves tend to rate other trauma victims more favorably.…”
Section: Stigma Gender and Ptsdsupporting
confidence: 90%
See 1 more Smart Citation
“…This finding supported previous research that has suggested that males are generally rated less favorably than females (Corrigan, Markowitz, Watson, Rowan, & Kubiak, 2003;Daoud, 2009;Snyder & Berscheid, 1977). Mendelsohn and Sewell (2004) also reported that women responded more favorably than men towards all victims, and those individuals who were rated as femininesex-typed rated victims more favorably than participants who were rated as being masculine-sextyped. This study also suggests that males who have been trauma victims themselves tend to rate other trauma victims more favorably.…”
Section: Stigma Gender and Ptsdsupporting
confidence: 90%
“…Currently, there is limited research specifically addressing the differences in perceived stigma surrounding males and females with PTSD. Mendelsohn and Sewell (2004) conducted a study that addressed social attitudes towards gendered responses to trauma. This study found that male victims were evaluated less favorably than female victims (Mendelsohn & Sewell, 2004).…”
Section: Stigma Gender and Ptsdmentioning
confidence: 99%
“…Traditional beliefs are also apparent in the expectations that the young men will have problems expressing feelings of sadness and fear, will be unable to identify themselves as crime victims, and will lack the support they ought to receive from their social network. In line with the study's theoretical premise that social interactions contribute to 'positioning' women and men in the gender order, Mendelsohn and Sewell (2004) suggest that meanings of traumatic events are tied to shared notions of what it means to be a man or a woman. It can be argued that characteristics that form the understanding of a 'normal' or 'ideal' victim to some extent are incompatible with notions of what it means to be a man (see e.g.…”
Section: Discussionmentioning
confidence: 66%
“…Research also shows that men who show signs of being in a stressful situation, such as signs of being traumatised, are at risk of being evaluated more negatively and considered to have more severe problems than women with the same symptoms (O'Neil, Good and Holmes 1995;Robertson and Fitzgerald 1990;Seem and Johnson 1998). Traumatised male victims of physical assault are also assessed less favourably (concerning likability, attractiveness as a friend and romantic partner, intelligence, and competence) than females in the same situation (Mendelsohn and Sewell 2004).…”
Section: Introductionmentioning
confidence: 96%
“…Those emotional responses that violate gender stereotypes often receive negative responses. Previous literature has also pointed out that those individuals who were more open or liberally minded in regard to gender stereotypes were generally more supportive to victims and less blaming than those who adhered to traditional sex role types (Mendelsohn & Sewell, 2004). In these studies, male participants were more judgmental toward trauma victims than female participants.…”
Section: Gender Role In Traumamentioning
confidence: 77%